Glanz und Elend der Aufklärung in Wien Voraussetzungen - Institutionen - Texte - Wolf, Norbert Christian (2023)
The Viennese Enlightenment began with a delay and then proceeded at an accelerated pace. The hurried and soon blocked process of adjustment led to peculiarities of Austrian culture. Based on the economic, political, social, medial and cultural conditions, the book presents exemplary debates and writings of this period and contextualizes them historically.